Oxidative stress pattern of patients with abnormal thyroid function in Southern Nigeria - Oloruntoba Festus; Ebenezer Dic-Ijiewere; Felix Ailemen; Nathaniel Imafidon; Joseph Ebo; Chikezie Nwankwo; Friday Iweka (Journal of Research in Applied and Basic Medical Sciences, 2025)
Background & Aims: In humans, oxidative changes have been associated with abnormal thyroid hormone levels. The aim of the study was to evaluate antioxidants and oxidative stress parameters in subjects with abnormal thyroid hormones in Irrua, Edo State. Materials & Methods: Two hundred samples were used for this study including 120 test subjects visiting the clinic with abnormal thyroid-related complaints and 80 healthy control groups. The triiodothyronine (T3), thyroxine (T4), thyroid stimulating hormone (TSH), malondialdehyde (MDA), reduced glutathione (rGSH), and catalase levels were determined using standard laboratory procedures. The results were presented in tables and charts as mean ± standard deviation. Results: Analysis of oxidative stress markers revealed that MDA levels in test subjects (4.9 ± 0.6) were not significantly different from the control group (4.7 ± 0.5; P = 0.77). Similarly, catalase activity in test subjects (216.9 ± 25.8) showed no significant difference compared to controls (178.6 ± 19.4; P = 0.29). However, rGSH levels were significantly lower in test subjects (74.8 ± 9.7) compared to controls (134.6 ± 9.7; p < 0.001). When analyzing thyroid function parameters, females with normal thyroid function exhibited significantly higher serum catalase levels (283.1 ± 38.9) compared to those with subclinical hyperthyroidism (101.5 ± 8.4) or hyperthyroidism (131.9 ± 13.0; P < 0.05). Among male participants, those with hyperthyroidism showed significantly lower rGSH levels (77.3 ± 23.5) compared to both males with subclinical hypothyroidism (186.0 ± 00.0) and healthy male controls (136.8 ± 7.7; P < 0.05). A key finding from this study is that thyroid dysfunction may not cause oxidative stress through lipid peroxidation. However, by the suppression of rGSH, this can have severe implications on the overall antioxidant defense system of the body predisposing it to oxidative damage and diseases. Conclusion: The findings of this study show that hyperthyroidism induces oxidative stress regardless of gender, which could play a major role in disease formation and other associated abnormal conditions.